15. Potency of Methanolic Extract of Sernai Stems (Wedelia biflora) as Analgesic on Mice (Mus musculus) - Annisa Rizka Rahmatia; Rinidar Rinidar; T. Armansyah TR; Rosmaidar Rosmaidar; Abdul Harris; Yudha Fahrimal (Universitas Syiah Kuala, 2018)
The purpose of this research was to determine the potency of methanolic extract of sernai stem (Wedelia bilflora) as analgesic to mice (Mus muculus) compared to ibuprofen. This research use split-plot method with 5 treatments and 5 replications. Group P0 as negative control was given aquadest, P1 as positive control was given ibuprofen, while P2, P3, and P4 were given the extract with dosage of 40, 50, and 60 mg/kg bw, respectively. The pain analysis of mice was conducted using hotplate method and the observation was carried out at 0 minute, 30 minutes, 60 minutes, 90 minutes, and 120 minutes. The data was analyzed using analysis of varians (Anova) followed by Duncan’s test. The results of this research showed that P1, P2, P3 and P4 had significant difference (P0,05) from P0. P1 did not have significant difference (P0,05) from P2 but it was different from P3 and P4 (P0,05). From this result we can conclude that methanolic extract of sernai stem was potential as analgesic, dosage of 40 mg/kg bw was equal to ibuprofen, while 50 mg/kg bw and 60 mg/kg bw showed better effect than ibuprofen.